THE INFLUENCE OF PSYCHOSOCIAL DEVELOPMENT ON SOCIAL STUDIES LEARNING OUTCOMES GRADE IV SD N 18 SUMBER MAKMUR - Sabrina Simbolon; Sapri Sapri (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2022)
The appropriate and directed psychosocial development of students has an effect on student social studies learning outcomes. Psychosocial development plays a crucial role in stimulating the nerves and muscles to encourage the psychosocial growth of students. The aims of this research are: (1) collecting data on psychosocial development, (2) collecting data on social studies learning outcomes for grade IV, and (3) understanding the extent to which psychosocial development impacts on social studies learning outcomes for grade IV students at SD N 18 Sumber Makmur. This study uses quantitative methods and pre-experimental design. The pre-experimental design applied in this study is the One-Shot Case Study. Questionnaires and tests were given to collect data in this research. Questionnaires were applied to collect data on psychosocial development, while tests were given to collect data on social studies learning outcomes. Regression analysis was applied to analyze the data. The research findings show that students' responses to psychosocial development are 64%, where this score is quite high because it is in the range between 60%-80%. While the average value of social studies learning outcomes is 84.2. Because tcount (4.673) is greater than ttable (2.101) in the regression test, then H0 is rejected, this indicates that psychosocial development has an influence on social studies learning outcomes. The variable of psychosocial development has a significant impact of 57.2% on social studies learning outcomes, while the remaining 42.8% is determined by other variables.